Optimizing resource utilization: palliative care consultations in critically ill pediatric trauma patients - Julie Goswami; Jacob Baxter; Brenda M Schiltz; Terri A Elsbernd; Grace M Arteaga; Denise B Klinkner (Trauma Surgery & Acute Care Open)
Objectives The American College of Surgeons Trauma Quality Improvement Program (TQIP) and Committee on Trauma released a best practice guideline for palliative care in trauma patients in 2017. Utilization of pediatric palliative care services for pediatric trauma patients has not been studied. We sought to identify patients who received the consultation and develop criteria for patients who would benefit from these resources at our institution.Methods The institutional pediatric trauma registry was queried to identify all admissions age 0–17 years old to the pediatric intensive care unit (PICU) or trauma ICU (TICU) from 2014 to 2021. Demographic and clinical features were obtained from the registry. Electronic medical records were reviewed to identify and review consultations to the ComPASS team. A clinical practice guideline (CPG) for palliative care consultations was developed based on the TQIP guideline and applied retrospectively to patients admitted 2014–2021. The CPG was then prospectively applied to patients admitted from March through November 2022.Results A total of 399 patients were admitted to the PICU/TICU. There were 30 (7.5%) deaths, 20 (66.7%) within 24 hours of admission. Palliative care consultations were obtained in 21 (5.3%). Of these, 10 (47.6%) patients were infants/toddlers <age 2 years, all had traumatic brain injury, 3 (14.3%) were for suspected child abuse, and many were for “goals of care” or family meetings. When the CPG was applied retrospectively, 109 (27.3%) patients met criteria for consultation. After 8 months of prospective implementation of this CPG, palliative care consultation was obtained in 25% (7 of 28) of pediatric trauma patients admitted to the ICU.Conclusion Our results demonstrate underused potential of the palliative care team to impact the hospital course of critically ill pediatric trauma patients. Ongoing studies will analyze the utility of CPG implementation for early involvement of palliative services in critically ill pediatric trauma patients.Level of Evidence Level III (retrospective cohort)